Evaluation of capsule labelling for its wall contents as gelatin or non gelatin - Gupta, Shallini; Khajuria, Kanika; Kumar, Niraj; Khajuria, Vijay (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Capsules are the most commonly used solid drug dosage form and are made up of gelatin or non gelatin. Currently the gelatin based capsules drug formulations are more used. However, current issue of vegetarian and non vegetarian capsules has come up due to recent Indian government initiative to promote vegetarian capsules. Methods: There were 100 capsule dosage forms were examined for the gelatin or HPMC wall contents and nature of medicine contained in capsules, whether ayurvedic or allopathic. Results: Out of 100 capsules studied 55 had gelatin wall base while 25 had HPMC and 20 capsule labels did not mention the nature of capsule wall constituent. Out of 55 gelatin capsules 30 were of allopathic while 25 capsules were of ayurvedic medicines. Among HPMC, 15 were ayurvedic while 10 allopathic. 20 capsules had no mention of its constituent and among these non labelled capsule formulations had 11 from ayurvedic and 9 from allopathic medicines. Conclusions: The current study revealed that gelatin capsules forms bulk in Indian market. Even the gelatin capsules contained ayurvedic medicines while 10% of HPMC capsules contained allopathic medicines. Non labelled capsules formed 20% of total capsules. These findings suggest wider scope for promotion of HPMC based capsules.